Peran Mubalighat dalam Pembentukan dan Pengembangan Qaryah Thayyibah di PCA Gegerbitung - rizqiani, Ika Sofia; Siwiyanti, Leonita; Suyaman, Prahasti; Sri Wahyuni, Yuyun (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This study aims to empower the women cadres of Aisyiyah in the Gegerbitung branch of Sukabumi Regency through Qaryah Thayyibah training, focusing on enhancing their knowledge, skills, and economic welfare. Methodology: The research employed Participatory Action Research (PAR) methodology involving planning, action, and reflection phases. Data collection instruments included pretest and posttest evaluations, direct observation, and participatory discussions. The study also utilized training sessions, mentoring, and community engagement as part of the intervention. Results: The findings indicate a significant increase in participants’ knowledge and skills across health, education, religion, social, and economic domains. The mentoring program successfully enhanced the independence of participants in managing family economic enterprises such as banana and cassava chips production. Conclusions: The implementation of PAR-based training and mentoring effectively improved the capacity and welfare of Aisyiyah women cadres, fostering a self-reliant and prosperous community in the Gegerbitung area. Limitations: The study was limited by its focus on a single community branch and a relatively short mentoring period, which may affect the generalizability and long-term impact assessment. Contribution: This research contributes to community development, women empowerment, and participatory methodologies in social and economic welfare enhancement within Islamic community organizations.